2023
DOI: 10.1186/s12864-023-09511-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of Enterococcus faecium strain RAOG174 associated with acute chorioamnionitis carried antibiotic resistance gene: is it time for precise microbiological identification for appropriate antibiotic use?

Abstract: Background Preterm labor syndrome is associated with high perinatal morbidity and mortality, and intra-amniotic infection is a cause of preterm labor. The standard identification of causative microorganisms is based on the use of biochemical phenotypes, together with broth dilution-based antibiotic susceptibility from organisms grown in culture. However, such methods could not provide an accurate epidemiological aspect and a genetic basis of antimicrobial resistance leading to an inappropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…Similarly, the VREfm isolates in the current study were resistant to ampicillin and quinolone, indicating a human-origin lineage. VREfm belonging to ST17 and ST80 have been reported worldwide, including in Germany (Neumann et al, 2020), France (Sassi et al, 2019), Australia (Lee et al, 2020), Libya (Ahmed et al, 2020), and Thailand, having been isolated from placental tissue, urine, blood, and rectal swabs (Wongnak et al, 2021;Pongchaikul et al, 2023). In Asia, ST17 and ST80 have been reported in China (Sun et al, 2019), India (Bakthavatchalam et al, 2022), and Taiwan (Kuo et al, 2018), whereas an outbreak of VREfm ST761 has been reported in France (Kamus et al, 2022), while ST117 has been identified in Denmark (Pinholt et al, 2019), Greece (Papagiannitsis et al, 2017), and Germany (Xanthopoulou et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the VREfm isolates in the current study were resistant to ampicillin and quinolone, indicating a human-origin lineage. VREfm belonging to ST17 and ST80 have been reported worldwide, including in Germany (Neumann et al, 2020), France (Sassi et al, 2019), Australia (Lee et al, 2020), Libya (Ahmed et al, 2020), and Thailand, having been isolated from placental tissue, urine, blood, and rectal swabs (Wongnak et al, 2021;Pongchaikul et al, 2023). In Asia, ST17 and ST80 have been reported in China (Sun et al, 2019), India (Bakthavatchalam et al, 2022), and Taiwan (Kuo et al, 2018), whereas an outbreak of VREfm ST761 has been reported in France (Kamus et al, 2022), while ST117 has been identified in Denmark (Pinholt et al, 2019), Greece (Papagiannitsis et al, 2017), and Germany (Xanthopoulou et al, 2020).…”
Section: Resultsmentioning
confidence: 99%